(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To assess the oral health status and analyze the relationship with oral care attitudes and behaviors in students of the Faculty of Dentistry, Van Lang University. Method: A cross-sectional study was conducted on 325 students of the Faculty of Dentistry, Van Lang University, from January to May 2024. Data were collected through self-administered questionnaires and clinical examination (SMTR, OHI-S index). Descriptive statistical analysis, Chi-square, Mann-Whitney U, and Kruskal-Wallis tests were applied. Results: The rate of dental caries was 22.5%, with an average SMTR index of 3.90 ± 3.76, which was higher in women than in men (p = 0.040) and increased gradually over the school year (p < 0.001). The mean OHI-S was 0.80 ± 0.56, with a higher plaque index in males (p = 0.001). Regarding behavioral factors related to oral health, male students had a lower frequency of toothbrushing and consumed more sugary foods, with statistical significance, than female students. Conclusion: The oral health of students of the Faculty of Dentistry, Van Lang University is still problematic, with differences between genders and cumulative by academic year. Behavioral factors were significantly associated with clinical outcomes, suggesting the need to enhance oral education and self-assessment in dental training programs.